Protocol for the design of an instrument to measure preadolescent children's self-report of covert aggression and bullying - Nelson, Helen; Kendall, Garth; Burns, Sharyn; Schonert-Reichl, K. (2015)
INTRODUCTION: Covert bullying in schools is associated with a range of academic, social, emotional and physical health problems. Much research has focused on bullying, but there remains a gap in understanding about covert aggression and how to most accurately and reliably measure children's own reports of this behaviour. This paper reviews relevant literature and outlines a research project that aims to develop a self-report instrument that effectively measures covert aggression and bullying. It is anticipated that this research will result in a standardised instrument that is suitable for exploring preadolescent children's experiences of covert aggressive behaviour. The data collected by the instrument will enhance health and education professionals understanding of covert bullying behaviours and will inform the design and evaluation of interventions. METHODS AND ANALYSIS: Relational developmental systems theory will guide the design of an online self-report instrument. The first phase of the project will include a critical review of the research literature, focus groups with children aged 8-12 years (grades 4-6) in Perth, Western Australia, and expert review. The instrument will be explored for content and face validity prior to the assessment of convergent and discriminant validity, internal consistency and test-retest reliability. ETHICS AND DISSEMINATION: The study has been approved by the Curtin University of Human Research Ethics Committee (RDHS-38-15) and by the Executive Principal of the participating school.